2014
DOI: 10.1111/iwj.12314
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of nebivolol and dexpanthenol on wound healing: an experimental study

Abstract: Wound healing is a dynamic, interactive process that is initiated in response to injury. A number of investigations and clinical studies have been performed to determine new approaches for the improvement of wound healing. The aim of this study was to compare the effects of dexpanthenol, a molecule that is widely used for improving wound healing, and nebivolol, a molecule that increases nitric oxide release, on wound healing. A total of 30 rats were divided into three equal groups (n = 10). A linear 2 cm incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Since dexpanthenol and allantoin showed no irritative reactions in the HET-CAM, both were considered to be possible additives for antiseptics in order to promote wound healing. 25,26 Furthermore, the antiseptic efficacy of chlorhexidine was increased by adding 5% dexpanthenol. 27 However, in our study the irritative effect of OCT was only slightly reduced by addition of 1.34% dexpanthenol and 0.2 allantoin.…”
Section: Discussionmentioning
confidence: 99%
“…Since dexpanthenol and allantoin showed no irritative reactions in the HET-CAM, both were considered to be possible additives for antiseptics in order to promote wound healing. 25,26 Furthermore, the antiseptic efficacy of chlorhexidine was increased by adding 5% dexpanthenol. 27 However, in our study the irritative effect of OCT was only slightly reduced by addition of 1.34% dexpanthenol and 0.2 allantoin.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of N‐acetylcysteine in wound healing was comparable with DEX (Oguz et al, ). Similarly, the wound healing rates of the DEX and nebivolol groups were high and comparable (Ulger et al, ). Furthermore, the combination of treatments of ultrasound and DEX accelerated collagen fiber synthesis and organization in the early stages of cutaneous repair (Guimarães, Pires‐De‐Campos, Leonardi, Dib‐Giusti, & Polacow, ).…”
Section: Vb5 and Wounds (Stitches)mentioning
confidence: 87%
“…More importantly, inhibition of this pathway can open new therapeutic approaches in SSc (Kavian et al, ). Calcium pantothenate modulates gene expression in proliferating human dermal fibroblasts (Wiederholt et al, ), and together with the high wound healing rates and effect on fibrosis of DEX (Ulger et al, ), new insight on a promising role in the treatment of SSc is provided. The vanin‐1 pathway, involved in VB5 generation, has a proinflammatory effect in many conditions including SSc (Bartucci et al, ; Kavian et al, ).…”
Section: B5 In Rheumatologymentioning
confidence: 99%
“…In a study by Ulger et al [21] which investigated the effects of the local application of nebivolol and dexpanthenol on wound healing, it was reported that although this administration significantly decreased inflammation compared with the control group, fibrosis in the dexpanthenol-treated group was higher. The same study also reported that granulation and angiogenesis rates did not differ significantly between the control and dexpanthenol groups [21]. The study emphasized that local administration of dexpanthenol might increase fibrosis by supporting tissue fibroblasts despite its anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%